ANALISIS STILISTIKA DALAM ALBUM LAGU MEMORANDUM KARYA GRUP BAND PERUNGGU - M, Muhammad Rajabbani; Sahlan Mujtaba; Dian Hartati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study focuses on the stylistic meaning in the form of figures of speech and imagery contained in the eleven songs in the Memorandum album by the Perunggu band. The researcher uses a qualitative descriptive method to analyze the stylistic meaning in the form of figures of speech and imagery elements in the Memorandum album by the Perunggu band. In this study, the researcher describes the results of the study of the Memorandum album by the Perunggu band according to the research object. Based on the results of the discussion of Stylistic Analysis in the Memorandum album by the Perunggu band, the following conclusions are obtained. 1. The results of the stylistic analysis in the form of figures of speech and imagery of the eleven songs in the Memorandum album by the Perunggu band provide quite diverse messages and meanings. Each of the eleven songs has its own uniqueness and diversity. 2. The results of the analysis show that there are 121 data that state figures of speech in the Memorandum album by the Perunggu band with the results of 88 data stating comparison figures of speech and 33 data stating link figures of speech. As well as 84 data that state the imagery on the Memorandum album by the band Perunggu.